A pressure-transient model for a fractured-vuggy carbonate reservoir with large-scale cave. Issue 2 (3rd March 2016) - Chen, Peng; Wang, Xinhai; Liu, Hong; Huang, Yongmei; Chen, Shuyang; Zhang, Hao
Abstract: In the development process of fractured-vuggy carbonate reservoir with large-scale caves, the location and size of cave affect the development program. This paper takes the large-scale cave as equipotential body, treats matrix and fracture as double porous media, and establishes the flow model. Laplace transform is used to simplify the model, and then the model is solved using boundary element method. Considering the wellbore storage effect and skin effect, the bottomhole pressure-transient curve is obtained using Stefest numerical inversion method. Comparing the results of analytical solution and boundary element method in the dual porosity medium illustrate the accuracy of this model. The sensitivity of cave parameters is analyzed. It shows that the larger the cave radius is, the stronger the convex and concave of curve is. The convex is earlier and concave is sooner when cave is closer to the well. The segment of convex keeps longer and the concave margin is greater with the larger compressibility ratio. Finally, as an application example, actual test data from a large-scale cave reservoir is analyzed using this model, and the location and size of cave are obtained. It has a certain significance for the reserve evaluation and well test in this reservoir.